Stairway to employment? Internships in higher education - Patrícia Catarina de Sousa e Silva (2016)
This article aims to shed light on the current debate regarding the role of internships in higher education in graduates’ employability. In specific, it analyses empirical data on a large-scale study of Portuguese first-cycle study programmes, in order to explore indicators of the professional value of internships in the employability of higher education graduates. Results demonstrate that study programmes that include internships tend to significantly enhance graduates’ employability, particularly within the universe of polytechnic and public higher education institutions. Besides the instrumental value of internships, the impact of the nature and structure of the internship on the percentage of unemployed graduates are also discussed. Mandatory internships and the inclusion of multiple, shorter internships throughout the degree are negatively associated with unemployment levels. Results indicate work-based learning can be used as a successful strategy to bridge theoretical knowledge and practice and enhance graduate employability. These findings provide important insights for the evaluation and/or the design of internship programmes in higher education.